The Voice of Labour: A Life in Toronto's Construction Industry - Toppan, Marino; Principe, Angelo; Breda, Paola; Frank Iacobucci Centre for Italian Canadian Studies (University of Toronto, Frank Iacobucci Centre for Italian Canadian Studies, 2019)
The memoirs of union organizer Marino Toppan, during the union organizing days of the residential construction "jungle" in Toronto: 1955-1980.
OCLC: 1137604231